TRANSLATION PROBLEMS OF DIPLOMATIC TERMS IN POLITICAL TEXTS - Almuratov Asqar Ravshan ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This study manages the issues connected with the interpretation of political texts in the hypothetical structure expounded by the analysts working in the field of interpretation studies and thinks about the expressed idiosyncrasies of the exceptional language utilized for this text type. Thought of the hypothetical system is trailed by the examination of a particular text spoken then written in English and converted into Hungarian and Romanian. The ends are expected to feature the way that there are no plans for interpreting a political discourse, since interpretation isn't just a specialized process that utilizes interpretation systems and applies move activities, however additionally a question of getting social, verifiable and political circumstances also, their importance.